"A Difficult Symbol for Women": The Garden Book and the Garden as Retreat in the Works of Rosamund Marriott Watson. Issue 1 (2nd January 2021) - O'Connell, Rachel
ABSTRACT: This essay considers how the Aesthete and poet, Rosamund Marriott Watson, explores the idea of the garden as retreat – a treacherously doubled symbol for women, both liberating and confining. In Marriott Watson's 1891 poetry collection A Summer Night, the garden retreat channels the transgressive energies of the 1890s, sheltering but continuous with the city, fostering the creative, sexually emancipated New Woman. By contrast, in her later garden book The Heart of a Garden (1906), Marriott Watson draws on the idea of the garden as retreat to present a valorization of insularity, withdrawal, and domesticity. This essay reads this change in garden ethos in relation to Marriott Watson's own career and also in terms of the conventions of the garden book (a little known genre that was popular at the turn of the nineteenth century). While the garden book has been read as feminist by recent critics, The Heart of a Garden reveals that, like the garden, the garden book carries double and ambivalent meanings. The essay closes by reading Marriott Watson's garden writing as a set of reflections on life in the suburbs, another site that was conceived, within the Victorian imagination, as a space of retreat.